2018
DOI: 10.1186/s10194-018-0880-0
|View full text |Cite
|
Sign up to set email alerts
|

Multigroup latent class model of musculoskeletal pain combinations in children/adolescents: identifying high-risk groups by gender and age

Abstract: BackgroundTo investigate the combinations of Musculoskeletal pain (MSP) (neck, shoulder, upper and low back pain) among a sample of Iranian school children.MethodsThe MSP combinations was modeled by latent class analysis (LCA) to find the clusters of high–risk individuals and multigroup LCA taking into account the gender and age (≤ 13 years and ≥ 14 years of age categories).ResultsThe lowest and highest prevalence of MSP was 14.2% (shoulder pain in boys aged ≥14 years) and 40.4% (low back pain in boys aged ≤13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…In five studies, the role of gender as a risk factor for LBP was mentioned [14,[15][16][17][18][19][20][21] . Although this study did not clearly identify which girls or boys were most at risk, only 2 studies reported a higher prevalence of LBP for boys [11,13] and one study reported a higher rate of LBP for girls [19] . But many studies around the world have shown that in addition to gender roles, girls have been more likely to have LBP [25][26][27][28] .…”
Section: Risk Factors Associated With Lbp In Children and Adolescentsmentioning
confidence: 71%
See 2 more Smart Citations
“…In five studies, the role of gender as a risk factor for LBP was mentioned [14,[15][16][17][18][19][20][21] . Although this study did not clearly identify which girls or boys were most at risk, only 2 studies reported a higher prevalence of LBP for boys [11,13] and one study reported a higher rate of LBP for girls [19] . But many studies around the world have shown that in addition to gender roles, girls have been more likely to have LBP [25][26][27][28] .…”
Section: Risk Factors Associated With Lbp In Children and Adolescentsmentioning
confidence: 71%
“…Boys were more likely to develop shoulder and back pain than girls. The results of this mentioned highlighted the importance to a more accurate understanding of gender and age-specific data [11] .…”
Section: In the Study Of Shamseddini Et Al (2009)mentioning
confidence: 88%
See 1 more Smart Citation
“…This allows a detailed comparison of different models based on goodness-of-fit statistics. [31][32][33] Third, in studies of the same pain syndromes, different types of variables were used to establish subgroups. 13 The most frequently used variables for statistical subgrouping were PRO measures, findings from physical examination (i.e., pain locations), 34 and diagnostic or experimental results (e.g., pain sensitivity ratings).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, a large number of school children have increasingly been adapted to use backpacks [5] , and carrying backpack has been a common practice of the daily work tasks among school going children [7,8] . Although based on studies, backpack is an appropriate way for carrying loads on the spine since they can distribute the load symmetrically with maintaining stability [9,10] , but extensive bag weight (when the weight of the bag exceeds 10% of the child's body weight), improper its handling, using non-ergonomic backpack, and long duration of school bag carrying might lead to MSDs among school age children [8,9,11] . In general, the researchers stated that because of the peak of growth occurs during adolescent [10] , students are susceptible to MSDs and it is one of the most important and common problems among them that its prevalence is increasing [5,9,[12][13][14] , and this rate is even higher because of the carrying of backpacks in these age groups [4] .…”
Section: Introductionmentioning
confidence: 99%